19th AIAA International Space Planes and Hypersonic Systems and Technologies Conference 2014
DOI: 10.2514/6.2014-2951
|View full text |Cite
|
Sign up to set email alerts
|

Mixing and Mass Exchange for Cavities in Supersonic Flows

Abstract: The ability of wall-mounted cavities to facilitate flameholding is largely dependent on local conditions within the recirculation region, that are, generally, vastly different from the adjacent supersonic flow. The local stoichiometry depends on the mixing within the flameholder and the mass exchange with the core flow. These processes are integrally linked to fuel injection location and its coupling with the recirculation region flow field. In the present study planar laser-induced fluorescence (PLIF) was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Liu et al [48] performed a RANS computation to examine the effect of fueling rate on the fuel distribution in a cavity with rear wall fueling and exposed to a Mach 2 airflow. Increased fueling progressively flooded the cavity volume and pushed the stoichiometric mixture fraction contour into the shear layer, similar to the experimental observations of Barnes et al [2] for the case of front wall fueling.…”
Section: Parallel Injectionsupporting
confidence: 74%
See 3 more Smart Citations
“…Liu et al [48] performed a RANS computation to examine the effect of fueling rate on the fuel distribution in a cavity with rear wall fueling and exposed to a Mach 2 airflow. Increased fueling progressively flooded the cavity volume and pushed the stoichiometric mixture fraction contour into the shear layer, similar to the experimental observations of Barnes et al [2] for the case of front wall fueling.…”
Section: Parallel Injectionsupporting
confidence: 74%
“…Yet as was reported by Barnes et al [2] in the study mentioned above, recirculation zone equivalence ratios may be up to an order of magnitude higher than indicated by global values. In this study [2] acetone-PLIF images for the case of parallel injection from the front cavity wall, as shown in Fig. 11, revealed that even for very small global equivalence ratios the majority of the cavity recirculation zone may be too rich for flameholding.…”
Section: Parallel Injectionmentioning
confidence: 60%
See 2 more Smart Citations
“…Gruber et al 12 investigated a supersonic cavity design using NO and OH PLIF, injecting reacting and non-reacting ethylene. Barnes et al 13 used acetone PLIF to determine fuel distribution in a directly injected cavity. Thakur et al 14 determined concentration distribution behind a cavity step.…”
Section: Figure 1: Lif Energy Diagrammentioning
confidence: 99%